Diagnosa Kecanduan Gadget Pada Anak Usia Dini dengan Metode Fuzzy Sugeno dan Fuzzy Mamdani - Rama Setiawan; Agung Triayudi; Arie Gunawan (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
The Tsukamoto fuzzy logic method is one method for problem solving control systems, which is good to implement with a system method that will use human knowledge that can be entered into the system on a computer to find and solve problems that usually require expertise or expertise. looking for a truth. The purpose of this study is to analyze and find methods that can be used in diagnosing gadget addiction in early childhood, and to compare two fuzzy methods that will be used as methods to diagnose gadget addiction in early childhood. The methods used in this study are expert system methods, namely fuzzy sugeno and fuzzy mamdani. The results showed that many children experience addiction to gadgets with a susceptibility to 1-4 hours of use time in one day. The level of addiction in boys is somewhat higher than in girls, the large number of children who are addicted to gadgets at a very early age to recognize and experience addiction to gadgets is the author's main goal to make this thesis if it can be used to monitor the level of gadget addiction in early childhood, research on the contribution of the method of applying the method the fuzzy sugeno and fuzzy mamdani algorithms in diagnosing gadget addiction in early childhood and the contribution to this method is the application of the fuzzy mamdani method and the fuzzy sugeno method to the fuzzy algorithm and the problem of this research is to determine the results of defuzzification of the data that has been obtained.